Occurrence and fate of tetracycline and degradation products in municipal biological wastewater treatment plant and transport of them in surface water - Topal, Murat; Topal, E. Isil Arslan (Springer, 2015)
The aims of this study are to investigate the fate of tetracycline (TC) and degradation products (DPs) in municipal biological wastewater treatment plant (MBWWTP) located in Elazig City (Turkey) and to determine the occurrence and transport of TC and DPs in surface water (SW) (Kehli Stream) which the effluents of the plant discharged. The aqueous phase removal of TC, 4-epitetracycline (ETC), 4-epianhydrotetracycline (EATC), and anhydrotetracycline (ATC) in the studied treatment plant was 39.4 +/- 1.9, 31.8 +/- 1.5, 15.1 +/- 0.7, and 16.9 +/- 0.8 %, respectively. According to the analyses' results of SW samples taken from downstream at every 500-m distance, TC and DPs decreased by the increase in the distance. In downstream, at 2000 m, TC, ETC, EATC, and ATC were 4.12 +/- 0.20, 6.70 +/- 0.33, 8.31 +/- 0.41, and 3.57 +/- 0.17 mu g/L, respectively. As a result, antibiotic pollution in the SW that takes the effluent of MBWWTP exists.
Keywords: Tetracycline; Surface water; Micropollutants; Antibiotic; Sludge; Turkey